Community based Economic-Development: Pertumbuhan Ekonomi Masyarakat Lokal Kota Batu Melalui Wisata Milenial Glow Garden - Saputra, Ridwan Hidayat; Rosyta Amalia Nakeisha; Veranjani Krisdyan Noorvita; Diva Zinta Ramadhani; Nafilla Dzakira Putri; Prisca Kiki Wulandari (JSE: Jurnal Sharia Economica, 2025)
Batu City has a very large potential for local economic growth through the tourism sector. One of them is the Millennial Glow Garden Tour located in Batu City, East Java. This destination has great potential to encourage local economic growth through the Community-Based Economic Development (CBED) approach. The Community Based Economic Development theory has 3 strategies including: Increasing Knowledge, Implementing Leadership Style, and Providing Assistance. In its implementation, the Millennial Glow Garden Tour only meets 2 of the 3 indicators of the Community Based Economic Development concept. This study aims to analyze local community empowerment strategies in developing community-based tourism to improve the welfare of local communities. This study uses qualitative methods through observation, interviews, and literature studies. The results of this study found that the Millennial Glow Garden has a positive impact through the provision of places and business permits for MSME actors, carnival events, which improve the welfare of local communities. However, challenges such as limited access to capital, minimal entrepreneurship training, and low community participation in planning still hinder equitable economic benefits.